Advancing ESP instruction through DDL: A structured training framework - Ammari, Maria (Glottodidactica, 2025)
This study explores the urgent need for corpus-based English instruction within English for Specific Purposes (ESP), an area with untapped potential despite its growing importance. The limited use of corpora in classrooms, due to shortcomings in teacher training, underscores the need for strategies that enhance teacher proficiency in corpus use, addressing the unique linguistic needs of learners. It proposes an integrated training framework, extending Carter and McCarthy’s (1995) ‘3 Is’, further expanded to ‘4 Is’ by Flowerdew (2009), to a more comprehensive training framework of ‘6 Is’ to facilitate a balance between inductive and deductive learning. The paper highlights the necessity of specialised training to empower teachers with the skills for effective Data-Driven Learning implementation in ESP teaching, aiming to improve the overall educational experience by integrating corpus insights into language instruction. Adopting a theoretical approach, this study synthesises insights derived from a specialised corpus and DDL pedagogy to develop a structured training framework. It provides a roadmap for ESP educators, equipping them with the necessary competencies to effectively integrate corpora into instruction. By offering a structured methodology, the study contributes to ongoing discussions on ESP teacher development and the normalisation of corpus-based teaching practices.